Student Creativity and Professional Artwork in a School Food Intervention in Denmark - Ruge, Dorte (Arts and Health Promotion: Tools and Bridges for Practice, Research, and Social Transformation, 2021)
The aim of this chapter is to present a case of an art-based initiative situated within a health-promoting school food project based in Denmark. The name of the project was “LOMA-local food” (LOMA = “lokal mad” in the original Danish), and its overall aim was to reduce inequity in health and learning via student development of food- and health-related action competence. This chapter applies social constructivist theory by Vygotsky and Freire on food in schools as a social practice, here integrated with student creativity and professional artwork in health promotion activities. From 2015 to 2017, 2754 students from five schools in four municipalities participated in the LOMA project. The main activities encompassed student participation in planning, cooking, and serving food for peers through cross-curricular activities. The case illustrates how the combination of teachers’ didactic work, student creativity, and professional artwork supported motivation, improved relationships, and nurtured the development of shared ownership among participants. The creative framework around LOMA activities constituted one element of a varied learning environment. According to the Danish Evaluation Institute, this contributed to a greater experience of enthusiasm and positive development in the social relations among participants in the LOMA project.